Involvement of the lateral entorhinal cortex for the formation of cross‐modal olfactory‐tactile associations in the rat. Issue 7 (14th May 2014) - Boisselier, Lise; Ferry, Barbara; Gervais, Rémi
ABSTRACT While the olfactory and tactile vibrissal systems have been extensively studied in the rat, the neural basis of these cross‐modal associations is still elusive. Here we tested the hypothesis that the lateral entorhinal cortex (LEC) could be particularly involved. In order to tackle this question, we have developed a new behavioral paradigm which consists in finding one baited cup (+) among three, each of the cups presenting a different and specific odor/texture (OT) combination. During the acquisition of a first task (Task OT1), the three cups were associated with the following OT combination: O1T1 for the baited cup; O2T1 and O1T2 for non‐baited ones. Most rats learn this task within three training sessions (20 trials/session). In a second task (Task OT2) animals had to pair another OT combination with the reward using a new set of stimuli (O3T3+, O4T3, and O3T4). Results showed that rats manage to learn Task OT2 within one session only. In a third task (Task OT3) animals had to learn another OT combination based on previously learned items (e.g. O4T4+, O1T4 and O4T1). This task is called the "recombination task." Results showed that control rats solve the recombination task within one session. Animals bilaterally implanted with cannulae in the LEC were microinfused with d‐APV (3 µg/0.6 µL) just before the acquisition or the test session of each task. The results showed that NMDA receptor blockade in LEC did not affect recall of Task OT1 but strongly impaired acquisition of both Task OT2 and OT3. Moreover, two control groups of animals infused with d‐APV showed no deficit in the acquisition of unimodal olfactory and tactile tasks. Taken together, these data show that the NMDA system in the LEC is involved in the acquisition of association between an olfactory and a tactile stimulus during cross‐modal learning task. © 2014 Wiley Periodicals, Inc.